Strengthening the Competence of History Teachers in Teaching Local History: Capacity Building Workshop for Subject Matter Teachers in Pasuruan City and Regency - Wahyudi, Deny Yudo; Wijaya, Daya Negri; Pratama, Andhika Yudha; Utari, Shela Dwi (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to strengthen teachers' ability to teach local history in schools by conducting workshops targeting history teachers in Pasuruan City and Regency. This activity is based on the results of a previous problem analysis, which shows that teachers still have difficulty obtaining local historical sources. Methodology: This study used a quantitative experimental method by treating teachers and observing the results through statistical data analysis. Main Findings: This study shows increased teachers' abilities after the workshop. This increase is proven by a t-test, which shows a difference between the pre-test and post-test scores of 6.57. At the end of the activity, participants were also given guidance on writing articles related to local history and integrating them into the independent curriculum. The findings of this study indicate that after attending the workshop, the participants, who were history teachers, experienced an increase in their understanding of local history. Novelty/Originality of this study: This study contributes to history learning and offers practical insights for improving the quality of history teachers.